Republic of Lithuania : Staff Report for the 2007 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
The 2007 Article IV Consultation discusses the Republic of Lithuania's economic developments and policy challenges. Lithuania has done well in the past years to improve its investment climate and ranks high on most measures of doing business. Enhancing flexibility is important because a quick response to changing European demand is key to maintaining the competitive advantage of Lithuanian producers. The income catch-up potential remains large, and the Lithuanian economy has demonstrated resilience to shocks and the ability to climb the technology and quality ladder.